Prediction and validation of sidesway collapse of two scale models of a 4-story steel moment frame. - Lignos, D. G. (Earthquake engineering & structural dynamics.)
A research program is summarized in which collapse of a steel frame structure is predicted numerically and the accuracy of prediction is validated experimentally through earthquake simulator tests of two 1:8 scale models of a 4-story code-compliant prototype moment-resisting frame. We demonstrate that (1) sidesway collapse can occur for realistic combinations of structural framing and earthquake ground motion; (2) P−Δeffects and component deterioration dominate behavior of the frame near collapse; (3) prediction of collapse is feasible using relatively simple analytical models provided that component deterioration is adequately represented in the analytical model; and (4) response of the framing system near collapse is sensitive to the history that every important component of the frames experiences, implying that symmetric cyclic loading histories that are routinely used to test components provide insufficient information for modeling deterioration near collapse.